Effect of Vocal Fry on Voice and on Velopharyngeal Sphincter - Elias, Vanessa Santos; Cielo, Carla Aparecida; Jotz, Geraldo Pereira; Christmann, Mara Keli (International Archives of Otorhinolaryngology, 2016)
Introduction It is known that the basal sound promotes shortening and adduction of the vocal folds and leaves the mucosa looser. However there are few studies that address the supralaryngeal physiological findings obtained using the technique.Objective To check the effectiveness of using vocal fry on the voice and velopharingeal port closure of five adult subjects, whose cleft palate has been corrected with surgery.Methods Case study with five subjects who underwent otolaryngology examination by means of nasopharyngoscopy for imaging and measurement of the region of velopharyngeal port closure before and after using the vocal fry technique for three minutes. During the exam, the subjects sustained the isolated vowel /a:/ in their usual pitch and loudness. The emission of the vowel /a:/ was also used for perceptual analysis and spectrographic evaluation of their voices.Results Four subjects had an improvement in the region of velopharyngeal port closure; the results of the spectrographic evaluation were indicative of decreased hypernasality, and the results of the auditory-perceptual analysis suggested improved overall vocal quality, adequacy of loudness, decreased hypernasality, improvement of type of voice and decreased hoarseness.Conclusion This study showed a positive effect of vocal fry on voice and greater velopharyngeal port closure.
Keywords: voice; cleft palate; sound spectrography; stomatognathic system abnormalities; velopharyngeal sphincter